EVALUATION OF HEALTH INTELLIGENCE STUDIES IN TURKEY - Muhittin Demi̇rkasimoğlu (Revija za kriminologiju i krivično pravo)
The last major epidemic, the COVID-19 pandemic, has revealed that there are many deficiencies in the health field. During the COVID-19 pandemic, as far as the media followed, many countries had difficulties accessing medical supplies, vaccines, and drugs and did not allow some medical products to leave the country. It has been observed that the necessary materials have disappeared with the work of the intelligence agencies of some countries. Politicians and scientists from many countries have put forth conspiracy theories about the source of the pandemic and the country of origin, and accusations have included claims about the use of biological weapons. This study aims to reveal what health intelligence is and what kinds of studies are done in Turkey and around the world. For this, the in-depth literature study of the case pattern study, one of the qualitative research methods, was used. In the analysis of the study, a descriptive analysis was made and the results were discussed.